2011
DOI: 10.1007/s11434-010-4501-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitooligosaccharides on cyclin D1, bcl-xl and bcl-2 mRNA expression in A549 cells using quantitative PCR

Abstract: Chitooligosaccharide (COS) is derived from the chemical and enzymatic hydrolysis of chitosan and has been reported to have potent antitumor activity. Our study investigated the effects of five chitooligomers ranging from the dimer form to the hexamer form (chitobiose, chitotriose, chitotetraose, chitopentaose, chitohexaose) on the expression of cyclin D1, bcl-2 and bcl-xl mRNA in A549 cells using reverse transcription quantitative real-time PCR. We demonstrated that, of the five chitooligomers used, chitohexao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The molecular weight of COS has an essential effect on anticancer activity. It has been reported that chitohexanoses are the most promising oligomers to manifest the anticancer effect (Xiong et al, 2009; Li et al, 2011). Wang et al (2007) published the results of studies confirming the influence of the degree of COS acetylation on anticancer activity.…”
Section: Biological Activity Of Chitin and Its Derivativesmentioning
confidence: 99%
“…The molecular weight of COS has an essential effect on anticancer activity. It has been reported that chitohexanoses are the most promising oligomers to manifest the anticancer effect (Xiong et al, 2009; Li et al, 2011). Wang et al (2007) published the results of studies confirming the influence of the degree of COS acetylation on anticancer activity.…”
Section: Biological Activity Of Chitin and Its Derivativesmentioning
confidence: 99%
“…The COS are currently commercialized and widely used in cosmetics, animal husbandry, medicine, and food industries. Many bioactivities of COS have been reported, including immunoregulatory [ 7 ], antioxidant [ 8 ], anti-tumor [ 9 ], anti-bacterial [ 10 ], antihypertensive [ 11 ], and anti-diabetes [ 12 ] activities, among others.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the antitumor activity of COSs, the influence of MW should also be taken into consideration in addition to the functional groups on the pyranose ring, including amino and acetyl amino groups [74]. Some studies have evaluated the antitumor differences between dimeric and hexameric COSs, with hexameric COSs showed the best effect on A549 cells [75]. In vitro studies have shown that COSs could exhibit antitumor activity on a variety of tumor cells, and in vivo experiments have shown that COSs could inhibit tumor proliferation and metastasis [76].…”
Section: Antitumor Activitymentioning
confidence: 99%